Nelson Glueck and King Solomon—A Romance That Ended (The Biblical archaeology review, 1975)
In 935, Nelson Glueck of Hebrew Union College conducted a survey of the Negev which astounded a generation of Bible students at what could be learned from surface finds alone. Among these finds in the Aravah rift (also found a year earlier by a German scholar Fritz Frank) were a large number of copper […]